Hipertensión arterial pulmonar - Dalmau, Ernesto; Arcila Quiceno, Victor Hernan (Spei Domus, 2007)
The cardiovascular system is important for the physiologic dynamics of biochemical processes as those carried out at lung level. The pathological changes associated to the arterial pressure have been studied and researched in different animal species including the humans. In many cases biomodels have been manipulated to obtain outstanding information regarding the physiopathologic and molecular mechanisms that bear the development of hypertensive states considering the cellular groups that participate of these events. The present document make a review on the possible mechanisms involved in the changes of the arterial pressure (hypertensive states) and its reference values considering diverse animal species.